2022
DOI: 10.1039/d1qi01625c
|View full text |Cite
|
Sign up to set email alerts
|

Exfoliation-induced O-doped g-C3N4 nanosheets with improved photoreactivity towards RhB degradation and H2 evolution

Abstract: Graphitic carbon nitride (g-C3N4) nanosheets exfoliated from bulk-sized counterparts are limited by quantum size effect-induced widened bandgap. In this work, a (NH4)2S2O8 (APS) induced thermal exfoliation approach is introduced to...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(12 citation statements)
references
References 49 publications
1
11
0
Order By: Relevance
“…situ plasma synthesis strategy also shows a high apparent quantum yield (AQY) of 4.14% at 450 nm, which is close to industrial utility [33]. With the help of theoretical calculation, we believe the improvement of hydrogen production performance of photocatalysts prepared by the plasma method is due to the favorable hydrophilic sites [34,35] and rearranged electronic structure [36,37] caused by carboxyl defects (Figure 8). The carboxyl defect sites may also promote the binding state of Pt cocatalysts for H2 generation.…”
Section: Visible-light-driven H 2 Evolution Performances and Optimiza...mentioning
confidence: 73%
See 1 more Smart Citation
“…situ plasma synthesis strategy also shows a high apparent quantum yield (AQY) of 4.14% at 450 nm, which is close to industrial utility [33]. With the help of theoretical calculation, we believe the improvement of hydrogen production performance of photocatalysts prepared by the plasma method is due to the favorable hydrophilic sites [34,35] and rearranged electronic structure [36,37] caused by carboxyl defects (Figure 8). The carboxyl defect sites may also promote the binding state of Pt cocatalysts for H2 generation.…”
Section: Visible-light-driven H 2 Evolution Performances and Optimiza...mentioning
confidence: 73%
“…As a result, more active sites for hydrogen production were developed, and thus both the H2O to H2 reaction and the H + to H2 reaction were boosted, leading to the superior H2 evolution performance. Based on the above experimental results, we believe that the plasma modification strategy proposed in this paper can effectively control the defect structure and electronic With the help of theoretical calculation, we believe the improvement of hydrogen production performance of photocatalysts prepared by the plasma method is due to the favorable hydrophilic sites [34,35] and rearranged electronic structure [36,37] caused by carboxyl defects (Figure 8). The carboxyl defect sites may also promote the binding state of Pt cocatalysts for H 2 generation.…”
Section: Visible-light-driven H 2 Evolution Performances and Optimiza...mentioning
confidence: 82%
“…In addition, introducing other non-metal elements are also effective strategies in promoting the photocatalytic property (Deng et al, 2019;Li et al, 2021b;Li et al, 2021c;Liu et al, 2021;Yan et al, 2022). For instance, carbon (C) self-doped g-C 3 N 4 was prepared via a combined method of melaminecyanuric acid complex supramolecular pre-assembly and solvothermal pre-treatment (Li et al, 2021b).…”
Section: Non-metal Dopingmentioning
confidence: 99%
“…The H 2 evolution rate for optimized g-C 3 N 4 was 18 times higher than that of bulk g-C 3 N 4 , and the enhanced performance derives from the extended optical absorption, accelerated photoactivated charge carrier separation, and transfer efficiency. Unique oxygen-doped g-C 3 N 4 materials were synthesized, which realized the synergetic control of the electronic structure and morphology and possessed the advantages of enlarged surface area, increased exposed active edges, and improved separation efficiency (Yan et al, 2022). Some other high-performance nonmetal doped materials including phosphorus-doped g-C 3 N 4 (Yang et al, 2018;Lin et al, 2020;Zhao et al, 2020) and sulfur-doped g-C 3 N 4 (Li et al, 2019a;Yang et al, 2020b;Long et al, 2020) have also been developed.…”
Section: Non-metal Dopingmentioning
confidence: 99%
“…[4] Converting inexhaustible solar energy into clean and stored hydrogen has been the focus of recent research. [5][6][7] The main task at this stage searches for highly efficient catalysts from non-noble metals and combine them with highly active photosensitizers (PS) into a reliable system for hydrogen production. [8,9] In recent years, it has been found that the photocatalysts, composed of transition metal complexes such as Fe, Co and Ni, are beneficial to the absorption of electrons because they have unfilled orbitals and can be used as separation centers for photogenerated electrons and holes, thus improving the activity of hydrogen production.…”
Section: Introductionmentioning
confidence: 99%